Deep-learning for epicardial adipose tissue assessment with computed tomography: implications for cardiovascular risk prediction - West, H; Antoniades, C; Siddique, M; Channon, K; Williams, M; Neubauer, S; Shirodaria, C; Thomas, S; Lyasheva, M; Dangas, K; Volpe, L; Kotanidis, C (Elsevier, 2023)
BACKGROUND: Epicardial adipose tissue volume (EAT) is a marker of visceral obesity that can be measured in coronary CT angiograms (CCTA). The clinical value of integrating this measurement in routine CCTA interpretation has not been documented.